Adsorptive Removal of Crystal Violet from Aqueous Solution Using Banana Pseudo Stem Biochar: Batch Adsorption Study - Karteyaini Baskaran; Noor Halini Baharim (Journal of Science and Technology, 2025)
Synthetic dyes, such as crystal violet (CV), are extensively employed in many industries and contribute major environmental risks when released into water bodies. Agricultural waste biochar has been investigated for dye removal; however, studies on banana pseudo stem (BPS) biochar are limited. In particular, studies using BPS biochar produced at higher pyrolysis temperatures are scarce. Therefore, this study explores the adsorptive removal of BPS biochar produced through slow pyrolysis at 500°C for 1 h, a temperature selected to enhance the surface area and porosity for the removal efficiency of CV from aqueous solution. The effects of operating adsorption parameters, such as solution pH, biochar dosage, initial dye concentration, contact time and temperature, were assessed by batch adsorption experiments. The maximum CV percent removal of 96.9% with 4.85 mg/g of adsorption capacity was achieved at optimal conditions of pH 6, 0.4 g of biochar dosage, an initial CV concentration of 20 mg/L, 90 min of contact time, and at the temperature of 35°C. For the adsorption isotherm study, the experimental results were better fitted to the Langmuir model with a maximum adsorption capacity of 23.09 mg/g. Meanwhile, the kinetic study was found to be best fitted to the pseudo-second-order model. BPS biochar prepared at elevated pyrolysis temperature is a sustainable and efficient alternative to conventional adsorbents. The remarkable removal efficiency under mild conditions, combined with using agricultural waste as adsorbent feedstock, demonstrates the BPS biochar for practical use in dye-contaminated wastewater treatment.